2005
DOI: 10.1126/science.1111199
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rotor Ring of F-Type Na + -ATPase from Ilyobacter tartaricus

Abstract: In the crystal structure of the membrane-embedded rotor ring of the sodium ion–translocating adenosine 5′-triphosphate (ATP) synthase of Ilyobacter tartaricus at 2.4 angstrom resolution, 11 c subunits are assembled into an hourglass-shaped cylinder with 11-fold symmetry. Sodium ions are bound in a locked conformation close to the outer surface of the cylinder near the middle of the membrane. The structure supports an ion-translocation mechanism in the intact ATP synthase in which the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
366
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(391 citation statements)
references
References 34 publications
24
366
0
1
Order By: Relevance
“…The rotation is biased to go in the required direction by the direction of the proton motive force across the membrane. Crystal structures of the proteolipid-ring complex from both V-and F-type ATPases show that the conserved protonatable residue of each monomer in the ring would be buried in a lipid bilayer with no direct accessibility of solvated protons to the residue (26,36). Therefore, in T. thermophilus, the I-subunit must contain both the periplasmic and the cytoplasmic half-channels that conduct protons to and from the Glu 63 residues of the ring.…”
mentioning
confidence: 99%
“…The rotation is biased to go in the required direction by the direction of the proton motive force across the membrane. Crystal structures of the proteolipid-ring complex from both V-and F-type ATPases show that the conserved protonatable residue of each monomer in the ring would be buried in a lipid bilayer with no direct accessibility of solvated protons to the residue (26,36). Therefore, in T. thermophilus, the I-subunit must contain both the periplasmic and the cytoplasmic half-channels that conduct protons to and from the Glu 63 residues of the ring.…”
mentioning
confidence: 99%
“…This architecture is also observed in the high-resolution X-ray structure of the subunit c oligomer from Ilyobacter tartaricus (Meier et al 2005), even though the relative orientation of the two helices and the conformation of polar loop are somewhat different. A remarkable feature of the NMR solution structure is that the helices fold together even though the number of interhelical contacts that may stabilize the hairpin structure is relatively small.…”
Section: Resultsmentioning
confidence: 71%
“…Model structures of the subunit c oligomer in E. coli were calculated from the solution structure of the subunit c monomer and extensive intersubunit cross-linking data (Dmitriev et al 1999b;Rastogi and Girvin 1999). Recently, a high-resolution structure of the subunit c oligomer from Ilyobacter tartaricus was solved by X-ray crystallography (Meier et al 2005).…”
mentioning
confidence: 99%
“…The c-subunit has a hairpin structure, which is composed of two a-helices and a connecting loop. Crystal structures of the F 1 -c-ring (34,35) and isolated c-ring (36)(37)(38) revealed that the c-subunits form a ring complex by assembling in a circle with the C-terminus pointing outward and the connecting loop toward the F 1 side (cytoplasmic side in bacteria) (Fig. 4).…”
Section: Structure Of F Omentioning
confidence: 99%